An archetypal case report of child abuse and neglect- a dentist's perspective - Gupta, Suruchi; Srivastava, Rashi; Sudhindra Baliga, M; Thosar, Nilima; Ghavat, Chinmay (Journal of Indian Academy of Forensic Medicine, 2020)
Child abuse and neglect are a serious global problem. It is often in the form of physical, sexual, emotional or neglect in providing for  the child's needs. In India, the number of cases registered for child abuse increased from 8,904 in the year 2014 to 14,913 in the year  2015 with more than half of the reported cases involving craniofacial trauma. In the present case report, a 10-year-old male child was  physically and emotionally abused by a senior schoolmate in the boys' hostel. In addition, neglect on the part of the hostel authorities  facilitated the abuse to cause more detrimental effects. The child reported with trauma and mental torture. With due management of  the trauma and debilitating emotional effects on the patient and providing counselling to the child and the caregiver, the patient made  a steady recovery. With this we can say that paediatric dentists come across children who may be victims and thus play a key role in  detecting child abuse and neglect as well as providing empathetic and appropriate care to them.
Keywords: Child abuse; Craniofacial trauma; Mental torture